2018
DOI: 10.3389/fgene.2018.00596
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Integrative Analysis of mRNA and microRNAs Expression Profiles and Epigenetic Alterations in Female SAMP8, a Model of Age-Related Cognitive Decline

Abstract: A growing body of research shows that epigenetic mechanisms are critically involved in normal and pathological aging. The Senescence-Accelerated Mouse Prone 8 (SAMP8) can be considered a useful tool to better understand the dynamics of the global epigenetic landscape during the aging process since its phenotype is not fully explained by genetic factors. Here we investigated dysfunctional age-related transcriptional profiles and epigenetic programming enzymes in the hippocampus of 2- and 9-month-old SAMP8 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 107 publications
(119 reference statements)
0
24
0
Order By: Relevance
“…These reports demonstrated that coadministration of these molecules induces a progressive, l-dopa-responsive PD which is preceded by gastric dysmotility (Anselmi et al, 2018). Finally, it is important to notice the role of the microbiota in the CNS, where the host is constantly controlling the maturation and function of the microglial cells (Cosin-Tomas et al, 2018), a reason to consider their effects and imbalances in the subject, which, in the future, could be key in the control, prevention, or even treatment of PD.…”
Section: The Neuroimmune Context Of Pdmentioning
confidence: 99%
“…These reports demonstrated that coadministration of these molecules induces a progressive, l-dopa-responsive PD which is preceded by gastric dysmotility (Anselmi et al, 2018). Finally, it is important to notice the role of the microbiota in the CNS, where the host is constantly controlling the maturation and function of the microglial cells (Cosin-Tomas et al, 2018), a reason to consider their effects and imbalances in the subject, which, in the future, could be key in the control, prevention, or even treatment of PD.…”
Section: The Neuroimmune Context Of Pdmentioning
confidence: 99%
“…In the 3xTg-AD mouse model, global methylation and hydroxymethylation levels are reduced (87). In the SAMP8 mouse model, global DNA methylation levels are decreased while 5-hmC levels are upregulated (88).…”
Section: Dna Methylation/ Hydroxymethylation In Admentioning
confidence: 99%
“…Thus achieving aging-associated molecular changes of the brain can provide a tool for distinguishing pathological amendments from normal ones. The miRNAs, as a part of epigenetic mechanisms, drastically contribute to cellular senescence, aging, and diseases (Cosín-Tomás et al, 2018).…”
Section: Aging and Mirnasmentioning
confidence: 99%
“…Thus achieving aging‐associated molecular changes of the brain can provide a tool for distinguishing pathological amendments from normal ones. The miRNAs, as a part of epigenetic mechanisms, drastically contribute to cellular senescence, aging, and diseases (Cosín‐Tomás et al, 2018). However, only a few miRNAs have been characterized by linking to the age‐related cellular or organic alternations (Luceri et al, 2017).…”
Section: Aging and Mirnasmentioning
confidence: 99%